2004
DOI: 10.1023/b:joih.0000019168.75062.36
|View full text |Cite
|
Sign up to set email alerts
|

Preimmigration Beliefs of Life Success, Postimmigration Experiences, and Acculturative Stress: South Asian Immigrants in the United States

Abstract: This study retrospectively explored the links between preimmigration beliefs of life success and postimmigration experiences and their influence on acculturative stress among a group of parents who recently immigrated with their children from three non-English speaking countries-Bangladesh, India, and Pakistan-to the United States. The respondents, 75 sets of parents residing in New York City, participated in semistructured qualitative interviews. Discrepancies between the parents' anticipated life success in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
104
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(110 citation statements)
references
References 5 publications
2
104
0
1
Order By: Relevance
“…Vartanian et al (2007) examined Japanese, Chinese, Korean, Filipino, Southeast Asian, and South Asian populations in NELS:88 data and found that South Asian students had the highest GPA amongst them. On the other hand, some qualitative studies warn the children of a recent subgroup of South Asian immigrants arriving since the mid-1980s face difficulty in adjustment to school and performance in school (Bhattacharya, 2000;Bhattacharya & Schoppelrey, 2004;National Asian Pacific American Community Development Data Center, 2005;Verma, 2008;Wright, 2007). This trend has not yet affected the achievement statistics for South Asians overall, but there is a possibility of lowered achievement levels in the future.…”
Section: Societal Receptionmentioning
confidence: 99%
See 4 more Smart Citations
“…Vartanian et al (2007) examined Japanese, Chinese, Korean, Filipino, Southeast Asian, and South Asian populations in NELS:88 data and found that South Asian students had the highest GPA amongst them. On the other hand, some qualitative studies warn the children of a recent subgroup of South Asian immigrants arriving since the mid-1980s face difficulty in adjustment to school and performance in school (Bhattacharya, 2000;Bhattacharya & Schoppelrey, 2004;National Asian Pacific American Community Development Data Center, 2005;Verma, 2008;Wright, 2007). This trend has not yet affected the achievement statistics for South Asians overall, but there is a possibility of lowered achievement levels in the future.…”
Section: Societal Receptionmentioning
confidence: 99%
“…India, Pakistan and Bangladesh once constituted one big nation under British rule, called India. In 1947, when British rule ended, the country was divided into the independent countries of India and Pakistan (Bhattacharya & Schoppelrey, 2004). The majority of Indians were Hindu while Bangladeshis and Pakistanis were predominantly Muslim.…”
Section: South Asian Immigration Historymentioning
confidence: 99%
See 3 more Smart Citations